ANALYSIS OF PROFITABILITY RATIO AS TOOL FOR ASSESSING THE PERFORMANCE OF THE BALITAR ISLAMIC UNIVERSITY OF BLITAR PERIOD 2016-2018 - Kismatul Ikodah; Diana Elvianita Martanti (Universitas Islam Balitar, 2020)
This study aims to determine the financial performance of Balitar Islamic University in the financial statements for 3 periods from 2016-2018. Based on the existing problems, the research used is descriptive method by collecting data, managing data and presenting research data / financial reports so that readers of this report can understand the description of the object of research data conducted at Balitar Islamic University in Blitar. Data analyzed were in the form of financial statements for three periods from 2016-2018 using profitability ratios. The results showed the net profit margin of the Islamic University of Balitar Blitar in 2016 was 0.8%, in 2017 it was 1% and in 2018 it was 1.1%. Judging from this percentage, net income has increased even though only slightly.